2017
DOI: 10.1111/ajo.12744
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic heart disease in pregnancy: How can health services adapt to the needs of Indigenous women? A qualitative study

Abstract: Despite previous studies documenting poor communication and culturally inadequate care, health systems did not meet the needs of pregnant Aboriginal women with rheumatic heart disease. Language-appropriate health education that promotes a shared understanding should be relevant to the gender, life-stage and social context of women with rheumatic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 20 publications
1
43
0
1
Order By: Relevance
“…Papers that called for improved clinician training in primary health settings to support cardiac disease detection/referral were mostly (5/6) published since 2014. Gaps in awareness among primary health care nurses (and women) were associated with delayed referrals and consistent with other studies that found women received contradictory advice and limited education . Language‐appropriate health education that promoted a shared understanding was largely absent for Aboriginal women with RHD …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Papers that called for improved clinician training in primary health settings to support cardiac disease detection/referral were mostly (5/6) published since 2014. Gaps in awareness among primary health care nurses (and women) were associated with delayed referrals and consistent with other studies that found women received contradictory advice and limited education . Language‐appropriate health education that promoted a shared understanding was largely absent for Aboriginal women with RHD …”
Section: Resultssupporting
confidence: 81%
“…The most common types of study design were cohort (19) and case series (20), with two qualitative studies, one cross‐sectional and one longitudinal screening study . There was considerable heterogeneity in the methodologies, levels of evidence, and reporting measures of these predominantly retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the lack of understanding and trust for Aboriginal women often results in service disengagement and non‐attendance to antenatal clinics, consequently increasing the risk of missed RHD diagnosis or severity . There is increasing evidence to suggest that maternity services that incorporate Birthing on Country principles, such as Aboriginal mothers and babies partnership models, have earlier and increased engagement along with improved maternal and perinatal outcomes . Appropriate preconception care provides opportunities to optimise cardiac status prior to pregnancy and offer medical and/or surgical intervention when appropriate, thus reducing morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This represents one of the highest burdens of RHD in the world. The consequences of ARF and RHD are enormous, significantly impacting, including shortening, the lives of Aboriginal and Torres Strait Islander children, adolescents, young adults, individuals, families and communities in Australia [8][9][10].…”
Section: Introductionmentioning
confidence: 99%